Language Maintenance Challenges and Successes: A Butonesse Student’s Story in the English Department at Pattimura University - Matatula, Marles Yohannis; Tupalessy, Pricilia (Huele: Journal of Applied Linguistics, Literature and Culture, 2023)
This study explores the challenges and strategies of Buton students in maintaining their local language in the academic environment. This study was conducted on January 7, 2023, at the English Education Study Program, Pattimura University, using a semi-structured interview method with a Buton student. The results showed that students faced obstacles such as the dominance of English and Indonesian on campus, the lack of peers with the same cultural background, and the lack of use of the Buton language in academic activities. The student used several strategies to overcome these challenges, such as speaking with family in Buton during phone calls or visits, teaching younger siblings traditional songs and phrases, and listening to local stories and songs. She also utilizes social media to share buton words or proverbs, so that the language remains in a modern context. This research shows that minority language preservation requires the support of families, communities, and educational institutions. Campuses can support these efforts by providing space for cultural activities, seminars, or linguistic communities. The maintenance of the Buton language helps students maintain their cultural identity while enriching diversity in the academic environment. This collaborative support is important to ensure the survival of language and culture in globalization.